Stone Circles near Shap, Westmoreland (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article describes some of the stone circles that can be found near the village of Shap in England. The author gives approximate circumferences for each stone circle and notes the difficulty of taking these measurements as many of the stones have fallen from their original positions. He does not offer any interpretation of who might have created these circles nor when or why they did so, but he does note that some of the stone circles he visited surrounded barrows containing human or animal remains. After his talk, members of the Society provided further examples of more sites like the ones described.